2017
DOI: 10.1089/ast.2016.1480
|View full text |Cite
|
Sign up to set email alerts
|

Kombucha Multimicrobial Community under Simulated Spaceflight and Martian Conditions

Abstract: Kombucha microbial community (KMC) produces a cellulose-based biopolymer of industrial importance and a probiotic beverage. KMC-derived cellulose-based pellicle film is known as a highly adaptive microbial macrocolony-a stratified community of prokaryotes and eukaryotes. In the framework of the multipurpose international astrobiological project "BIOlogy and Mars Experiment (BIOMEX)," which aims to study the vitality of prokaryotic and eukaryotic organisms and the stability of selected biomarkers in low Earth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…Previous work has shown that a KMC normally forms a biofilm within 2 days postinoculation; however, it can take up to 2 months to form biofilm in stress-exposed KMC samples (Podolich et al, 2017a(Podolich et al, , 2017b. In this study, during the recovery process, the KMC samples that had returned from LEO and also the laboratory and transportation control samples, as well as ground-based experiment ones, had completely blackened and become nontransparent after 7 days of culturing.…”
Section: Survival Of the Kmc Communitymentioning
confidence: 74%
See 3 more Smart Citations
“…Previous work has shown that a KMC normally forms a biofilm within 2 days postinoculation; however, it can take up to 2 months to form biofilm in stress-exposed KMC samples (Podolich et al, 2017a(Podolich et al, , 2017b. In this study, during the recovery process, the KMC samples that had returned from LEO and also the laboratory and transportation control samples, as well as ground-based experiment ones, had completely blackened and become nontransparent after 7 days of culturing.…”
Section: Survival Of the Kmc Communitymentioning
confidence: 74%
“…The cultures were grown until pellicles were formed, which were *0.7 mm in diameter. The pellicles were mixed with an anorthosite egg white mixture to ensure that the culture was integrated with the mineral samples and desiccated, as described (Podolich et al, 2017a). The samples were shipped from Kyiv to the German Aerospace Center (DLR) in Cologne.…”
Section: Biomineral Sample Preparation and Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Under ideal conditions these materials could be biodegradable and the thus obtained biomass could be returned to the circulation by being re-used in bioreactors. To make it possible, it seems optimal to use natural fabrics which are almost always biodegradable (Béguin and Aubert 1994;Li et al 2010;Podolich et al 2017Podolich et al , 2019.…”
Section: Introductionmentioning
confidence: 99%